Feasibility Sheet for the Program the Maritime Technological Surveillance carried out through Sensor Networks based on Fixed and/or Semi-fixed Unmanned Platforms (Global Journals of Research in Engineering, 2023)
The DETECTION in the present case indicates the discovery but not the location POSITIONING which may or may not be followed by subsequent locations in a tracing eventuality The last certain position of the target is defined in the air and naval field as DATUM In the current geostrategic scenario the threat must only be seen in a direct war confrontation In the other sense the target in the DPE Triangle enlarges the concept threat In fact in the rescue missions of human life at sea the threat must be understood only as the impediments to act to complete the rescue